2009
DOI: 10.1371/journal.pone.0005596
|View full text |Cite|
|
Sign up to set email alerts
|

Intention Understanding in Autism

Abstract: When we observe a motor act (e.g. grasping a cup) done by another individual, we extract, according to how the motor act is performed and its context, two types of information: the goal (grasping) and the intention underlying it (e.g. grasping for drinking). Here we examined whether children with autistic spectrum disorder (ASD) are able to understand these two aspects of motor acts. Two experiments were carried out. In the first, one group of high-functioning children with ASD and one of typically developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 45 publications
6
89
1
Order By: Relevance
“…In the literature, right-lateralized effects of action observation have been found in tasks that contained features of prediction in time of the outcome of the action or of the final intention of the agent (Iacoboni et al 2005;Hamilton and Grafton 2008;Liepelt et al 2008). These tasks are clearly different from the one of the present experiment, which consists in recognizing ''what'' an observed agent is doing in that exact moment as opposed to ''why'' the agent is doing it (Boria et al 2009). Aside from imaging experiments, however, prior to the present study, a causal role of the inferior parietal cortex in action coding has been suggested only by human lesional studies (Heilman et al 1982;Rothi et al 1985).…”
Section: Discussioncontrasting
confidence: 62%
“…In the literature, right-lateralized effects of action observation have been found in tasks that contained features of prediction in time of the outcome of the action or of the final intention of the agent (Iacoboni et al 2005;Hamilton and Grafton 2008;Liepelt et al 2008). These tasks are clearly different from the one of the present experiment, which consists in recognizing ''what'' an observed agent is doing in that exact moment as opposed to ''why'' the agent is doing it (Boria et al 2009). Aside from imaging experiments, however, prior to the present study, a causal role of the inferior parietal cortex in action coding has been suggested only by human lesional studies (Heilman et al 1982;Rothi et al 1985).…”
Section: Discussioncontrasting
confidence: 62%
“…Therefore, the intentions of others do not 'intrude' into the mirror system of children with ASD and these intentions are not understood 'from the inside' but only 'from the outside'. This interpretation is supported by a recent study showing that to understand the intentions of other people, children with ASD do not rely on the observed motor behaviour but on the semantics of the object that is being manipulated or on the context in which the motor act takes place 125 . Figure is Such motor-based understanding seems to be a primary way in which individuals relate to one another, as shown by its presence not only in humans and monkeys, but also in evolutionarily distant species, such as swamp sparrows 4 and zebra finches 5 .…”
Section: Discussionmentioning
confidence: 59%
“…More recently, a study by Boria,FabbriDestro, Cattaneo, Sparaci, Sinigaglia, Santelli,et al (2009) demonstrated poorer understanding of subsequent actions in children with autism. In this study, children were shown static images of a hand either touching an object, grasping-to-use it or grasping-to-place it.…”
Section: Behavioural Studies Of Action Understanding In Autismmentioning
confidence: 99%